2014
DOI: 10.1016/j.celrep.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

PAS Kinase Drives Lipogenesis through SREBP-1 Maturation

Abstract: Summary Elevated hepatic synthesis of fatty acids and triglycerides, driven by hyperactivation of the SREBP-1c transcription factor, has been implicated as a causal feature of the metabolic syndrome. SREBP-1c activation requires the proteolytic maturation of the endoplasmic reticulum-bound precursor to the active, nuclear transcription factor, which is stimulated by feeding and insulin signaling. Here we show that feeding and insulin stimulate the hepatic expression of PASK. We also demonstrate, using genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 47 publications
2
51
1
Order By: Relevance
“…Former observations have reported that inhibiting several regulators (including FAS, SREBP-1C) hinders liver lipid deposition in obesity and its associated symptoms [43][44][45]. In this study, we found that S100A4 deficiency caused elevated accumulation of liver fat, and that led to elevated CHO and TG (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Former observations have reported that inhibiting several regulators (including FAS, SREBP-1C) hinders liver lipid deposition in obesity and its associated symptoms [43][44][45]. In this study, we found that S100A4 deficiency caused elevated accumulation of liver fat, and that led to elevated CHO and TG (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…3A). Interestingly, the WT PASK associated with KD mTOR showed significantly diminished phosphorylation at Thr 307 , which is an autophosphorylation site that we have shown previously to be a reliable marker of PASK activity (31). Thus, expression of KD mTOR suppresses PASK activity in a dominant negative manner in cells.…”
Section: Pask Is Phosphorylated By Mtorc1 At Multiple Residues To Stimentioning
confidence: 55%
“…Such a concept is supported by the results of recent studies on SREBP inhibitors in animal models [43][44][45][46]. Here, we briefly describe the SREBP maturation pathway, elaborate key molecular mechanisms involved in the classical triad of hyperglycemia, hyperinsulinemia, and hypertriglyceridemia, and discuss beneficial effects of four SREBP inhibitors as well as potential caveats associated with their use.…”
mentioning
confidence: 88%
“…Pharmacological inhibition of PASK was utilized to inhibit SREBP-1 activity in the third study [45]. Earlier research had shown that protection from HFD-induced liver steatosis is a main phenotype of Pask -/-mice [41].…”
Section: Pask Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation